Optimasi PID Kontrol BLDC Menggunakan Metode Ziegler-Nichols - Muhammad Nabel Al Fayyed; Rifdah Mayhasna Nur Alayya; Wildan Abu Bakar Sidiq; Tatyantoro Andrasto (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2025)
This research focuses on optimising precise Brushless DC (BLDC) motor speed control using a Proportional-Integral-Derivative (PID) controller. The fundamental problem lies in the performance of PID control, which is highly dependent on the accuracy of determining its gain parameters (Kp, Ki, Kd), where manual tuning methods often do not provide satisfactory results. Therefore, the objective of this study is to apply the Ziegler-Nichols systematic method to the PID control tuning process for BLDC motors and then evaluate the performance of the resulting system based on key response time parameters such as rise time, settling time, overshoot, and steady-state error. The proposed method involves designing a mathematical model of the BLDC motor and applying the Ziegler-Nichols technique, specifically the Ultimate Oscillation Method, to systematically derive the values of Ku and Pu which are then used to calculate Kp (5.1), Ki (22.7), and Kd (0.29). The main findings show a dramatic performance improvement in the BLDC speed control system after the implementation of the tuned PID; the rise time is significantly reduced from 0.3728 seconds (without PID) to 0.0041 seconds, the settling time improves from 0.6642 seconds to 0.0073 seconds, and most importantly, the steady-state error of 45.38% is eliminated to 0%. The main idea synthesis is that the Ziegler-Nichols method provides an effective and practical approach to PID parameter optimization, resulting in a highly responsive, accurate and stable BLDC motor control system. In conclusion, this study successfully demonstrates that applying a PID controller with parameters determined via the Ziegler-Nichols method significantly improves the speed control quality of a BLDC motor, overcoming the steady-state error problem and substantially improving the transient response characteristics.